Efficiency of moringa oleifera seeds for treatment of laundry wastewater - Abduh Algheethi, Adel Ali Saeed; RMSR, Mohamed; Wurochekke, A. A.; Nurulainee, NR; Mas Rahayu, J; Hashim, MK (EDP Sciences, 2017)
Laundry wastewater has simple characteristics in which the detergents compounds are the main constitutes. But these compounds have adverse effects on the aquatic organisms in the natural water bodies which received these wastes without treatment. Few studies were conducted on these wastes because it represent a small part of the total wastewater generated from different human activities. Moreover, the coagulation process for laundry wastewater might be effective to remove of detergents compounds. Therefore, in the present study, the efficiency of coagulation process by using chemical (ferrous sulphate) and natural coagulants (Moringa oleifera seeds) were investigated. The raw laundry wastewater samples were collected from laundromat located at Taman Universiti, Parit Raja. The characteristics of these wastes were determined and then the wastewater was subjected for the treatment process consisted of three units including aeration, coagulation and sedimentation process. The chemical and natural coagulants were used with four dosage (30, 60, 90 and 120 mg L-1) and the coagulation process was carried out at room temperature (25±2ºC) for one hour. The results revealed that the laundry wastewater have high concentrations of turbidity (57.8-68.1 NTU) and Chemical Oxygen Demand (COD) (423-450 mg L-1) with pH value between 7.96 and 8.37. M. oleifera seeds exhibited high efficiency for removal of turbidity (83.63%) with 120 mg L-1 of dosage, while 30 mg L-1 of FeSO4 was the best for removal of COD (54.18%). However, both parameters still more than Standard B for wastewater disposal suggesting the need to increase the period of coagulation process with M. oleifera seeds or to subject of the treated effluents for a secondary coagulation process with natural coagulant products to improve the characteristics of laundry wastewater without a secondary products as that generated with the chemical coagulants.